Observations on the mobilization of peat nitrogen in incubation experiments - Jaakko Kivekäs; Erkki Kivinen (Scientific Agricultural Society of Finland, 1959)
60 peat samples from northern Finland representing different types of peat were incubated in a laboratory at a temperature of 17—18° C. The ammonium nitrogen, the nitrate nitrogen and the pH in the samples were determined after one month of incubation as well as after three months of incubation. The results were compared to results from determinations made before incubation. An attempt was made to elucidate the factors that influence the mobilization of nitrogen. On the basis of the above results it is evident that the differences between the various peat types as mobilizers of nitrogen are under these circumstances not very distinct, nor do these differences seem to be dependent on the types of peat. The following facts can, however, be established: In the amounts of ammonium nitrogen an increase takes place in most groups of samples during the first month. This increase is fairly big in the Sphagnum-dominated peats. The increase in ammonium nitrogen continues in the unlimed samples in most peat groups during all three months of incubation. After three months of incubation the amount of ammonium nitrogen in the limed samples is smaller than in the unlimed samples, although it is usually bigger than in the original samples. After the first month of incubation the amounts of nitrate nitrogen in all types of peat have decreased compared to the amounts in the original samples. In the limed samples the decrease is not as great as in the unlimed ones. After three months of incubation the amount of nitrate nitrogen has considerably increased as compared to the amount after one month of incubation. In the limed samples it might to some extent exceed the original amount of nitrate nitrogen, however, this is seldom the case in the unlimed samples. If the results are calculated on the basis of weight unit, it can be stated that the ability to mobilize nitrogen is greater in the Sphagnum peats than in the other peat groups. Working out the results in kg per ha it will be noted that somewhat more nitrogen is mobilized in ...